Post annealing induced magnetic anisotropy in CoFeSi thin films on MgO(0 0 1). (1st February 2017) - Guo, X B; Zuo, Y L; Cui, B S; Li, D; Yun, J J; Wu, K; Wang, T; Xi, L
Abstract: Co61 Fe26 Si13 (CoFeSi) thin films were deposited on MgO(0 0 1) substrates by magnetron sputtering and were annealed at different temperatures ( T a ). X-ray diffraction revealed that the crystal structure varies from the as-deposited amorphous phase to the cubic phase when T a = 800 °C, indicating the re-crystallization process after annealing treatment. The static magnetic property measurements show a gradually four-fold cubic anisotropy dominating the magnetic anisotropy with the increasing T a . The ferromagnetic resonance technique based on vector network analyzer was utilized to analyze the dynamic magnetic properties. CoFeSi film annealed at 600 °C presents an obvious in-plane uniaxial magnetic anisotropy, and it presents a low effective damping constant of around 0.011 with a natural resonance frequency of around 3.4 GHz. However, the CoFeSi film annealed at 800 °C showed a strong cubic magnetocrystalline anisotropy and full-in-plane-direction workable natural resonance frequency at around 2.5 GHz.